Properties of Two Broad Host Range Phages of Yersinia enterocolitica Isolated from Wild Animals - Jens A. Hammerl (MDPI AG, 2021)
Yersinia (Y.) enterocolitica and Y. pseudotuberculosis are important zoonotic agents which can infect both humans and animals. To combat these pathogens, the application of strictly lytic phages may be a promising tool. Since only few Yersinia phages have been described yet, some of which demonstrated a high specificity for certain serotypes, we isolated two phages from game animals and characterized them in terms of their morphology, host specificity, lytic activity on two bio-/serotypes and genome composition. The T7-related podovirus vB_YenP_Rambo and the myovirus vB_YenM_P281, which is very similar to a previously described phage PY100, showed a broad host range. Together, they lysed all the 62 tested pathogenic Y. enterocolitica strains belonging to the most important bio-/serotypes in Europe. A cocktail containing these two phages strongly reduced cultures of a bio-/serotype B4/O:3 and a B2/O:9 strain, even at very low MOIs (multiplicity of infection) and different temperatures, though, lysis of bio-/serotype B2/O:9 by vB_YenM_P281 and also by the related phage PY100 only occurred at 37 °C. Both phages were additionally able to lyse various Y. pseudotuberculosis strains at 28 °C and 37 °C, but only when the growth medium was supplemented with calcium and magnesium cations.